Re-Desain Website Cv Planktoon Dengan Metode Up Selling Dikombinasikan Dengan Sosial Media Untuk Peningkatan Penjualan - Willybrodus, Malkus; Sukmaaji, Anjik; Soebijono, Tony (JAVA Journal of Electrical and Electronics Engineering, 2015)
Website of CV. Planktoon currently not focusing in interests and satisfaction of customer evidenced by don’t have a membership system. Website does not create variations of offer and services to customers. The website also does not provide a direct link between the amount of stock the products in the store with the stock on the website so some reservations sometimes have problems delay or even cancellation of orders due to the number of stocks do not conform or perish. Lack of dissemination of information about the products (new products) causes a lack of interest and the interest of the consumer to visit a website so that the website the less popular or less visited by customers. The owner also had difficulty in preparing reports sales transactions that contain sales reports, daily stock, sales turnover and the best-selling items. In addressing these problems, made a re-design of website system which capable of providing a recommendation as to similar products through strategies of Up Selling, have a member registration features, dissemination of product information via sosial media, have a product search feature, ordering and payment until the confirmation of data delivery to the customer, and make a reports sales transactions that contain sales reports, daily stock, sales turnover and the best-selling items to owner. From the test results, the system is able to generate output rekomedasi up selling products, dissemination of product information via sosial media, member registration feature, and produce reports like sales reports, daily stock, sales turnover and the best-selling items